Trait modelling for stress tolerance in Indian mustard : Evidenced from seedling stage (Journal of Oilseed Brassica, 2026)
The current scanty knowledge about the physiological mechanisms underlying plants’ ability to tolerate salt stress that hinders potential production of numerous crops, including mustard. To explore the traits and mechanism for salt tolerance in mustard, we used 250 stabilized F7:8 recombinant inbred lines (RILs) mapping population developed by crossing indigenous contrasting genotypes CS 614-1-1-100-13 (salt sensitive) × CS 56 (salt tolerant) and evaluated them under control and irrigated water salinity of ECiw 12 dS/m to characterize for growth, photosynthetic and ionic traits. Step wise regression revealed, instantaneous water use efficiency, transpiration rate and fresh weight of root together accounted for more than 93% of the overall variation in photosynthesis rate under salt stress condition, indicating their critical contribution to reducing salt stress. The salt tolerance index (STI) categorized 23 RILs as salt tolerant, 99 RILs as moderately tolerant and remaining 128 RILs were sorted as salt sensitive RILs. These identified salt tolerant RILs can be exploited for QTLs and gene discovery and serve as potential doners/future ready lines to combat abiotic stress and development of salt tolerant varieties of mustard.